PENGARUH PERGANTIAN KURIKULUM KTSP MENJADI KURIKULUM 2013 - Audri Alfirdausy, Farhan; Kurniawan, Naufal (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
Curriculum as a written plan of learning (educational document). The curriculum as a written plan has a certain format. In Indonesia, we know the matrix format used by the 1975 curriculum, the 1986 curriculum, the 1994 curriculum, and so on Changes in the curriculum from the original KTSP to the 2013 curriculum caused many changes and influences in learning. The goal to be achieved in this study is to analyze the effect of changing the KTSP curriculum to K13 in elementary schools. With the interview method at one of the teachers and educational institutions, it is hoped that this can be used as an analysis for this curriculum change. This research was motivated by the implementation of the 2013 curriculum at all levels of education, both at the elementary, junior high, and high school levels. Teachers face many problems in implementing the 2013 curriculum, especially the revised 2013 curriculum applied at MIM 11 Sumberagung. This research is a qualitative research with descriptive method. This study aims to identify problems faced by teachers in implementing the revised 2013 curriculum in elementary schools. This study concludes that not all problems faced by teachers are due to errors in the 2013 curriculum, but teachers must also be able to maximize their professional abilities to answer the challenges in the 2013 curriculum.Keywords : : Curriculum Change, KTSP Curriculum, 2013 Curriculum